Fabrication and characterization of starch/zein nanocomposites with pH-responsive emulsion behavior. (March 2021) - Li, Songnan; Huang, Liang; Zhang, Bin; Chen, Chun; Fu, Xiong; Huang, Qiang
Abstract: Hydrophobic modified starch nanoparticles were fabricated through combined starch nanoprecipitation and complexation with zein, and their emulsifying behaviors were further evaluated as a Pickering emulsion stabilizer. Novel starch/zein nanocomposites with a unimodal particle distribution, mean diameter of 147.9 nm and contact angle of 83.0° were achieved. Fourier transform-infrared spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, differential scanning calorimetry, and confocal laser scanning microscopy demonstrated that the zein was successfully complexed with the starch molecules. Dissociation test confirmed that electrostatic interaction and hydrogen bonding were the main driving forces for the formation and maintenance of the starch/zein nanocomposites. Complexing with zein endowed the starch nanoparticles with emulsion pH-responsive behavior, which could provide a simple and green pathway to pH-responsive materials that afford controlled release of bioactive ingredients with emulsion delivery and recyclable catalysis of enzymatic reactions. Graphical abstract: Image 1 Highlights: Novel starch/zein nanocomposites were successfully fabricated. Complexation with zein achieved hydrophobic modification of starch. Starch/zein ratio and reverse method dominated the formation of nanocomposites. Starch/zein nanocomposites exhibited emulsion pH-responsive behavior.